Teachers' Questioning Strategy to Teach Speaking at MA An-Nidhomiyah - Imam Syafi'i; Hendra Sudarso (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2022)
This study aims to describe the implementation and the students’ responses toward the use of questioning strategy in teaching speaking. The research design of the study was qualitative which focus on case study research. It involved the eleventh-grade students of MA An-Nidomiyah as the subject of the research. The data were obtained through the observation during the teaching and learning process and an interview with the students. In this study, the researcher accomplished several steps to analyze the data, namely organizing and familiarizing, coding and reducing, interpreting, and representing. The result of the research finding proves that it is effective to use this strategy. So, using a questioning strategy can improve speaking skills and knowledge of vocabularies. Furthermore, it is suggested that questioning strategy can be effectively used in speaking class.